Attentional Orientation Patterns toward Emotional Faces and Temperamental Correlates of Preschool Oppositional Defiant Problems: The Moderating Role of Callous-Unemotional Traits and Anxiety Symptoms - Susa Erdogan, Georgiana; Benga, Oana; Marină, Crina (Frontiers in Psychology, 2017)
The present study examined the independent contributions and the interaction effects of oppositional defiant problems (ODD), callous unemotional traits (CU) and anxiety symptoms on attentional orienting to emotional faces, in a community sample of preschoolers. Additionally, based on Rothbart's (2007) model of temperament, we analyzed whether fine-grained dimensions of reactivity (fear, anger, discomfort, sadness, activity level, approach, high intensity pleasure, impulsivity) and self-regulation (attentional shifting, attentional focusing, inhibitory control), as well as the higher order temperamental factors of negative affectivity, surgency and effortful control are associated with CU traits and ODD - related problems. Attentional orienting to emotional faces was assessed with pictorial Dot-probe task, while teachers rated CU traits and ODD - related problems. Also, parents reported on ODD - related problems, anxiety and temperament. Results indicated significant interaction effects between ODD - related problems and CU, as well as between CU and anxiety, in predicting attentional orientation patterns for angry, fearful and happy faces. Moreover, temperamental reactivity was positively associated with CU traits and ODD-related problems, whereas temperamental self-regulation was negatively related to CU traits and ODD – related problems. Results of this study have implications for early intervention and prevention approaches targeting preschool oppositional defiant problems.